Analisis Strategi Penjualan Produk Saridele Menggunakan Metode SWOT dan BCG pada UMKM Saridele Segan - Sugiarto, Vito Andrianto Pratama; Pratama, Andreas Dhiyong; Ishaq, Ardan Maulana; Saputri, Aisyatul Widad; Fitriani, Anisa Putri; Amalia, Dewi; Hariastuti, Ni Luh Putu (Industrial Engineering Study Program, Pattimura University, 2025)
Soy milk is an alternative drink to replace cow's milk, and it is popular because it is highly nutritious. The availability of market opportunities for this substitute product is the basis for designing a business development strategy for Saridele Segan MSMEs through a SWOT analysis approach and the Boston Consulting Group (BCG) matrix. This study aims to formulate strategies and evaluate product positions in a business portfolio based on relative market share and market growth rate. SWOT analysis is used to identify the strengths, weaknesses, opportunities, and threats faced by this MSME. At the same time, the BCG matrix helps determine the optimal strategy for products in the Stars, Cash Cows, Question Marks, and Dogs categories. The study results indicate that Saridele Segan MSMEs are in quadrant 1 of the SWOT matrix and quadrant II of the Question Mark BCG group. The selected strategy refers to the SO strategy. Namely, an aggressive strategy to expand the market by maximizing the potential of superior products through the exploitation of Cash Cows to support investment in Question Marks and increase competitiveness through product innovation and operational efficiency. The integrated SWOT and BCG approach provides a practical strategic framework for the sustainability of Saridele MSMEs in a more competitive market.